THE FUNCTION OF SYNTACTIC DEVICES IN THE SYNTACTIC DESIGN OF ADVERTISING TEXTS: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article investigates the function of syntactic devices in the formulation of advertising texts. Through an exhaustive examination, the research endeavors to elucidate the manner in which syntactic structures enhance the efficacy of advertisements in communicating messages and impacting consumer behavior. By scrutinizing extant academic literature and employing qualitative research methodologies, this study offers significant insights into the syntactic composition of advertising discourse.